2008
DOI: 10.1039/b716979e
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of DiI-C18(3) in a DPPC lipid bilayer

Abstract: We performed a 40 ns simulation of 1,1'-dioctadecyl-3,3,3',3'-tetramethylindocarbocyanine perchlorate (DiI-C18(3)) in a 1,2-dipalmitoyl-sn-glycero-3-phosphatidyl choline (DPPC) bilayer in order to facilitate interpretation of lipid dynamics and membrane structure from fluorescence lifetime, anisotropy, and fluorescence correlations spectroscopy (FCS). Incorporation of DiI of 1.6 to 3.2 mol% induced negligible changes in area per lipid but detectable increases in bilayer thickness, each of which are indicators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
119
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(137 citation statements)
references
References 56 publications
17
119
1
Order By: Relevance
“…The hydrophobic alkyl chains insert into the lipophilic core of phospholipid bilayers, whereas the positively charged fluorophore rests close to the polar head groups, parallel to the membrane surface (2,13). This binding mechanism makes them excellent probes for lipidic membranes, a property that made dialkylcarbocyanines attractive as fluorescent probes to detect extracellular vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrophobic alkyl chains insert into the lipophilic core of phospholipid bilayers, whereas the positively charged fluorophore rests close to the polar head groups, parallel to the membrane surface (2,13). This binding mechanism makes them excellent probes for lipidic membranes, a property that made dialkylcarbocyanines attractive as fluorescent probes to detect extracellular vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…This interdigitation of alkyl or acyl chains of long-tailed solutes has been observed previously in MD simulation studies. [68][69][70] Fig . 3 Average transverse position hzi of specific POPC and sterol atoms in the simulations of systems containing none or two sterol molecules (A) and 20 mol% sterol (B).…”
Section: Areas Per Lipid and Bilayer Thicknessmentioning
confidence: 99%
“…The emission dipole is oriented along the short molecular axis of the head group and is known to be almost parallel to the excitation dipole [26]. Molecular dynamics (MD) simulations of the dye incorporated into a lipid membrane revealed that the dye molecule is located below the lipid-water interface [28] and therefore shielded from interactions with water molecules. As a result, the fluorophore is highly fluorescent and photo stable only within the membrane [26,29].…”
Section: Introductionmentioning
confidence: 99%